Algunos hongos hipogeos interesantes para la micoflora catalana - Vidal i Frigola, Josep Maria (Revista Catalana de Micologia, 2007)
Some interesting hypogeous fungi of the catalan mycoflora (Catalonia, Spain). Fourteen species andone variety of hypogeous fungi are studied (1 zygomycete, 6 ascomycetes and 8 basidiomycetes). Nineof them are new records for the Iberian flora, namely: Endogone nammicorona, Hydnotrya michaelis, Tuber malençonii, T. rufum var. nigrum, Chondrogaster paehysporus, Hymenangium album,Hymenogaster Iycoperdineus, Hysterangium nephriticum and Setehelliogaster tenuipes. Most species aredescribed, and illustrated with M.O. photographs. New data of their ecology and phenology are provided.